Being, machine and the solitude: Her, by Spike Jonze - Fioruci, Wellington Ricardo (Journal 2i: Identity and Intermediality Studies, 2019)
This paper aims at analyzing the movie Her, directed and scripted by the American realizer Spike Jonze in 2013, considering to explore the relationship between society and technology proposed by the cinematographic work. In that respect, the solitude problematic of the individual and the conflict related to alterity stand out in the movie which are enhanced and mediated by the relationship of the man with technology, important themes to the contemporary society.